Gut microbial communities of Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.) in the East Gallatin River - Rodriguez, Maria L; Maritan, Andrew J; Verhille, Christine E; Stewart, Frank J; Keil, Deborah E; Armijo, Augustus; Pratte, Zoe A (Frontiers in Marine Science, 2025)
The gastrointestinal (GI) microbiome plays a critical role in animal health and fitness, yet it remains understudied in many species—particularly those inhabiting freshwater environments affected by anthropogenic activity. This study investigates the gut microbiomes of two benthic fish species, Rocky Mountain Sculpin (Cottus bondi) and suckerfish (Catostomus spp.), collected upstream and downstream of a wastewater treatment plant (WWTP) effluent outflow into the East Gallatin River in southwestern Montana. Prokaryotic and eukaryotic microbiome diversity in the fish GI tract was assessed using 16S and 18S rRNA gene sequencing, respectively, from samples collected in the summer and fall of 2022 and 2023. While alpha diversity only had insignificant and small shifts across samples, beta diversity (taxonomic composition) differed significantly across sites and collection dates. Notably, the composition of eukaryotic sequences shifted markedly from upstream to downstream locations, suggesting that WWTP effluents may influence both prokaryotic and eukaryotic microbial communities. By establishing baseline GI microbiome characteristics for these species, this study provides important insights into the potential ecological effects of wastewater discharge on freshwater systems and supports conservation efforts aimed at mitigating pollutant impacts.